Conclusion: The future of research into language learning strategies - Pawlak, Mirosław; Oxford, Rebecca L. (Studies in Second Language Learning and Teaching, 2018)
In this concluding paper to the special issue (SI) we seek to achieve three main goals. First, based on the papers it included in the SI, other recent publications as well as our own ideas, we point to the future directions of research into language learning strategies. Second, we comment upon the methodological issues that such research inevitably has to face, stressing in particular the need to combine a macro-and micro-perspective. Third, we emphasize the pedagogical orientation of such empirical investigations and make a plea for intensive efforts on the part of specialists to find ways in which the findings of LLS research can in fact inform classroom pedagogy.